2006
DOI: 10.1063/1.2210080
|View full text |Cite
|
Sign up to set email alerts
|

La 0.7 Sr 0.3 Mn O 3 nanoparticles coated with fatty amine

Abstract: We report on the synthesis of La0.7Sr0.3MnO3 (LSMO) nanoparticles having perovskite structure and particle size of the order of 30nm. The process involves citrate-gel synthesis, size filtering, and surface coating with a shell of octadecyl amine (ODA) using electrostatic interaction-assisted novel chemical route. Magnetic measurements show the Curie temperature of ∼360K establishing the desired stoichiometry and phase. Fourier transform infrared studies bring out that the amine group of ODA interacts with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 26 publications
2
22
0
Order By: Relevance
“…The lower saturation moment of Dex-LSMO could be attributed to their smaller size and the influence of coating on magnetization of the nanoparticles. Such magnetization drops have been reported after coating of LSMO with octadecylamine 30 or coating of iron oxide nanoparticles with silica. 31 Hysteresis loops (inset to Figure 5) revealed that LSMO and Dex-LSMO were predominantly ferromagnetic at room temperature.…”
Section: Vibrating Sample Magnetometrymentioning
confidence: 97%
“…The lower saturation moment of Dex-LSMO could be attributed to their smaller size and the influence of coating on magnetization of the nanoparticles. Such magnetization drops have been reported after coating of LSMO with octadecylamine 30 or coating of iron oxide nanoparticles with silica. 31 Hysteresis loops (inset to Figure 5) revealed that LSMO and Dex-LSMO were predominantly ferromagnetic at room temperature.…”
Section: Vibrating Sample Magnetometrymentioning
confidence: 97%
“…It should be noted that only some physical properties of nanopowdered La 0.7 Sr 0.3 MnO 3 (LSMO) manganites were studied in a few papers [4][5][6][7][8]. The nanocrystallites were shown to exhibit properties that are significantly different from those of the bulk material.…”
Section: Introductionmentioning
confidence: 96%
“…Although this article does not include a study of toxicity, we will note some essential points. Many experiments on the coating La–Sr manganites with biocompatible shells including SiO 2 , dextran, citrate ligands, fatty amines, polyvinylpyrrolidone (PVP), etc. proved the colloidal stability and biocompatibility of LSMO NPs.…”
Section: Numerical Results and Discussionmentioning
confidence: 99%